Impact of Protein Source and Its Levels on Egg Production and Egg Quality of Japanese Quail (Coturnix coturnix japonica) - Salih, Jameela H.; Mohammed, Dejeen A.; Hussen, Shekhmous H. (Science Journal of University of Zakho, 2021)
Fish and soybean meal are known as common utilized crude protein sources in poultry diets. Quail birds often need higher requirements of dietary protein which influences its productive performance. The aim of the experiment is to determine the impact of protein source with different levels on egg production and egg quality characteristics. The experiment was carried out at animal production dept., University of Duhok, Kurdistan Region- Iraq, during spring 2020 for 56 days. The birds were divided into two main groups (fish meal and soybean meal) with three levels of crude protein (CP) as sub groups (20%, 23% and 26%). At 35 days of age, 240 quails were sexed and distributed on wire cages as four replications for each protein level within each group (treatment) as family (8 pullets with 2 cocks). The investigated characters were; Egg weight (EW), egg number (EN), egg mass (EM), egg quality characteristics (shape index, high, weight and diameter of both, yolk and albumen, egg shell thickness and weight and Haugh units); feed intake (FI), feed conversion ratio (FCR), hatchability and fertility percentage. The main results were as follows; EW, EM and most of egg quality characteristics did not show significant difference (P>0.05) either by source of protein or its levels; also, FI and FCR did not differ significantly (P>0.05) by the effect of protein source; while EN, FI and FCR were affected significantly (P≤0.05) by CP level. To conclude, there was no obvious trend for the effect of both CP source and level on early egg yield and egg quality in J. quail.